Polemik Mahkamah Kontitusi Terhadap Pertimbangan Open Legal Policy dalam Putusan Perkara Perpanjangan Masa Jabatan Pimpinan Komisi Pemberantasan Korupsi (KPK) - Haidir Madan, Muhammad Rechanda (UNES Law Review, 2023)
The importance of the Constitutional Court giving birth to decisions that contain substantial justice to what the community needs, one of which is to examine the law against the 1945 Constitution (UUD 1945). The authority of the Constitutional Court is actually allowed to go beyond what is stated in the law, only if the law confines the Constitutional Court judges in upholding justice such as Positive Legislature. In Decision Number 112/PUU-XX/2022, the Constitutional Court granted a judicial review request against Law Number 19 of 2019. One of the Court's decisions was to grant a change in the term of office of the KPK leadership, which was originally 4 years to 5 years in one term. This decision is actually the domain of lawmaking institutions, the Constitutional Court's view on open legal policy is part of a policy whose domain is outside of its competence in several specific articles in the law. Open legal policy actually needs to be given a limit by reflecting on its practice and foundation in several countries. This research uses a doctrinal research method which is a library legal research conducted by examining library materials or secondary data which is then supported by comparative studies of various countries. The results showed that the Constitutional Court should have rejected this case because it is an open legal policy that should be returned to the authority of the legislature. The Constitutional Court's decision on the extension of the KPK's term of office is controversial because it violates the principle of division of powers in state institutions. Its consideration was also not based on the urgent interests of citizens. Therefore, the author compares the practice with other countries, such as the United States, which overcomes the open legal policy gap with the use of the political questions doctrine, which provides clear boundaries to see a moment when the judiciary must take action with the orientation of restoring citizens' rights, and when it must refrain according to the concept of separation of powers. However, other countries such as Poland, Ukraine and Hungary have used open legal policy as a tool to reduce political attacks on the constitutional judiciary.